What 3 consecutive integers equal 9?
Now I know the answer is 2+3+4 but, how would I write it?
I would right it like this:
Let X equal the second integer
3X = 9
3X ÷ 3 = 9 ÷ 3
X = 3
Therefore the first integer is 3 - 1 = 2 and the second integer is 3 + 1 = 4
Is this the correct way of writing it? I don't wanna get marks off for writing it incorrectly. If it is incorrect how can I change it to write it correctly?
Thanks :)
Now I know the answer is 2+3+4 but, how would I write it?
I would right it like this:
Let X equal the second integer
3X = 9
3X ÷ 3 = 9 ÷ 3
X = 3
Therefore the first integer is 3 - 1 = 2 and the second integer is 3 + 1 = 4
Is this the correct way of writing it? I don't wanna get marks off for writing it incorrectly. If it is incorrect how can I change it to write it correctly?
Thanks :)
-
Let x be the first of the consecutive integers. The statement says :
--------------------------------------…
[ x ] + [ x + 1 ] + [ x + 2 ] = 9
3x + 3 = 9
x = 2 <-----------------------------------
x + 1 = 3 <-----------------------------
x + 2 = 4 <-------------------------------------
The consecutive integers are [ 2 , 3 , and 4 ] <----------------------
I turned the word statement into an equation. This takes practice , but is most
worthwhile.
--------------------------------------…
[ x ] + [ x + 1 ] + [ x + 2 ] = 9
3x + 3 = 9
x = 2 <-----------------------------------
x + 1 = 3 <-----------------------------
x + 2 = 4 <-------------------------------------
The consecutive integers are [ 2 , 3 , and 4 ] <----------------------
I turned the word statement into an equation. This takes practice , but is most
worthwhile.
-
You would have to show the representation of the 3 numbers..
as...
We consider the 2nd number to be X
Thus, 1st number : X - 1
3rd number : X + 1
Thus, according to the given condition,
( X -1 ) + X + ( X + 1 ) = 9
3 X = 9
And then continue with the solution you have written....
as...
We consider the 2nd number to be X
Thus, 1st number : X - 1
3rd number : X + 1
Thus, according to the given condition,
( X -1 ) + X + ( X + 1 ) = 9
3 X = 9
And then continue with the solution you have written....
-
x+1 + x + x-1 = 9
3x = 9
x = 3
x-1 = 2
x+1 = 4
2, 3, 4
only difference is that that is showing x is the middle integer. you could also to x + x+1 + x+2 = 9 where x is the first integer.
3x = 9
x = 3
x-1 = 2
x+1 = 4
2, 3, 4
only difference is that that is showing x is the middle integer. you could also to x + x+1 + x+2 = 9 where x is the first integer.
-
x + (x+1) + (x+2) = 9
solving for "x" which is the first integer
solving for "x" which is the first integer